Role of Lactobacillus in Female Infertility Via Modulating Sperm Agglutination and Immobilization - Zhang, Fenghao; Dai, Jie; Chen, Tingtao (Frontiers in Cellular and Infection Microbiology, 2021)
Infertility has become a common problem in recent decades. The pathogenesis of infertility is variable, but microbiological factors account for a large proportion of it. Dysbiosis of vaginal microbiota is reportedly associated with female infertility, but the influence of normal vaginal microbiota on infertility is unclear. In this review, we summarize the physiological characteristics of the vaginal tract and vaginal microbiota communities. We mainly focus on the bacterial adherence of vaginal Lactobacillus species. Given that the adherent effect plays a crucial role in the colonization of bacteria, we hypothesize that the adherent effect of vaginal Lactobacillus may also influence the fertility of the host. We also analyze the agglutination and immobilization effects of other bacteria, especially Escherichia coli, on ejaculated spermatozoa, and speculate on the possible effects of normal vaginal microbiota on female fertility.